(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم الاقتصادية والقانونية, 2019)
لقد احتلت التنمية الاقتصادية أهمية بالغة وأصبحت هدفاً رئيساً لمعظم دول العالم سواء المتقدمة منها أم المتخلفة ، وخاصة بعد الحرب العالمية الثانية، إذ نالت معظم الدول استقلالها السياسي , وسعت الدول العربية لتحقيق تنميتها الاقتصادية والاجتماعية؛ لذلك كان لا بدّ من توفير مصادر التمويل اللازمة من أجل تحقيق هذه التنمية ، فلجأت إلى مصادر التمويل الداخلية، ومن أهمها : الادخار والضرائب . ولكن نتيجة ضعف الموارد المحلية ، وعدم كفايتها اضطرت إلى اللجوء إلى مصادر التمويل الخارجية بالرغم ممّا تشكله هذه المصادر من عبء اقتصادي وسياسي واجتماعي . ويأتي الاقتراض الخارجي ـ وخاصة من مؤسسات التمويل الدولية و في مقدّمتها البنك الدولي ـ من أهمّ مصادر التمويل الخارجية . ولكنّ شروط تلك المؤسسات لم تكن مواتية ،فكان لمشكلة المديونية الخارجية آثار اقتصادية واجتماعية وسياسية على الدول العربية . The economic Development have taken deep importance, and has become a major goal of most States, whether developed or undeveloped, especially after the second world war where most States gained political independence, extended Arabic States (especially non-oil) to achieve its economic and social development, therefore, must provide the necessary funding to achieve development, resorted to internal sources of funding: savings and taxes, but as a result of weak domestic resources and inadequate had to resort to external sources of funding despite danger These sources from the burden of economic, political and social, and particularly external borrowing comes from international finance institutions and in particular the World Bank is one of the most important external sources of funding, but their conditions were not favorable, and the problem of external indebtedness and economic effects on the social and political Arabic States